Development and internal validation of a nomogram for predicting 90-day poor functional outcome after mechanical thrombectomy in very elderly patients - Dewang Pan; Zhiguo Li; Junfeng Zhao; Liyu Xia; Huaiyu Niu; Yang Zheng; Shuangxu Tan; Yu Li; Guoliang Li; Ying Liu (Medicine, 2026)
Mechanical thrombectomy (MT) is increasingly performed in very elderly patients with acute ischemic stroke, but individualized in-hospital prognostic assessment after treatment remains limited, particularly after early postprocedural events have become clinically apparent. This study aimed to develop and internally validate a nomogram for predicting 90-day poor functional outcomes in very elderly patients after MT. We retrospectively enrolled very elderly patients (aged ≥ 80 years) with acute ischemic stroke who underwent MT at a single center between January 1, 2020 and August 1, 2025. Poor functional outcome was defined as a modified Rankin Scale score of 3 to 6 at 90 days. Candidate predictors, including baseline, peri-procedural, and early postprocedural variables, were screened using univariable logistic regression and incorporated into a multivariable model. Because complete separation was observed for collateral status, the final model was constructed using Firth penalized logistic regression. Model discrimination was assessed using the area under the receiver operating characteristic curve, calibration was evaluated by the Brier score, calibration intercept, and calibration slope, and internal validation was performed with bootstrap resampling. Clinical utility was assessed using decision curve analysis. A total of 214 patients were included, of whom 80 (37.4%) had poor outcomes and 134 (62.6%) had good outcomes at 90 days. The final nomogram incorporated 6 predictors: National Institutes of Health Stroke Scale score at admission, diabetes mellitus, puncture-to-recanalization time, postoperative pneumonia, symptomatic intracranial hemorrhage (sICH), and poor collateral status. The model showed good discrimination, with an area under the curve of 0.874 (bootstrap 95% confidence interval, 0.811–0.929). Calibration was acceptable, with a Brier score of 0.112, a calibration intercept of 0.057, and a calibration slope of 1.090. Decision curve analysis demonstrated a meaningful net benefit across threshold probabilities ranging from 0.01 to 0.99. We developed and internally validated a nomogram for predicting 90-day poor functional outcomes in very elderly patients after MT. This model may assist in-hospital prognostic stratification, risk communication, and discharge planning in already treated patients after early postprocedural complications have been identified or excluded. However, it was not designed for pretreatment decision-making or for estimating the treatment effect of endovascular therapy.